Vascular Repair and Remodeling: A Review - Renna, Nicolas Federico (2018)
Cardiovascular diseases (CVDs) such as ischemic heart disease (IHD), stroke, and peripheral artery disease (PAS) are the leading cause of mortality and morbidity around the world: about 30% of global deaths and 10% of global disease burden a year are due to CVDs.In this chapter, we will analyze the classic concepts of vascular remodeling, to later expand the concepts and physiopathological mechanisms of vascular inflammation. The role of immunomodulation from IL-6R alpha and the JAK / STAT3 intracellular cascade, as an activator of vascular remodeling mechanisms. In addition, the role of new drugs such as LCZ696 and immunomodulators involved in the local inflammatory response will also be analyzed.The concept of remodeling and vascular inflammation, which a decade ago was only important at the level of basic research, step by step has proved crucial in the appearance of atherosclerosis, called subclinical atherosclerosis. Much progress has been made in the treatment and discovery of pathophysiological mechanisms, rest improve the studies of deterrence and its correlation with the reduction of cardiovascular risk, this is perhaps, the decade in which we can advance in this.